2018
DOI: 10.3126/jjis.v6i0.19314
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Problem among School-going Adolescents in Pokhara, Western Nepal

Abstract: Adolescence the second decade of life is the crucial period demanding significant adjustment to the physical and social changes. During this transitional period, if adequate care and attention is not given adolescents are prone to develop various psychosocial problems with long standingimpact. This descriptive cross-sectional study was conducted to assess the prevalence of psychosocial problem and its associated factors among 360 adolescents studying in public schools of Pokhara Lekhnath Metropolitan City. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
3
9
1
Order By: Relevance
“…This perception significantly associated with anxiety and depression (p=0.026 and p=0.013), which is following other studies. 18,19 The presence of any chronic illness in the family was found to be significantly (p=0.003) associated with the presence of anxiety and it was in accordance with another study 20 . In the present study, ease to discuss problems with parents and perceiving unnecessary restrictions were both found to be significantly associated with anxiety (p<0.001) as well as depression (p=0.004), which was per the findings of another study.…”
Section: Discussionsupporting
confidence: 87%
“…This perception significantly associated with anxiety and depression (p=0.026 and p=0.013), which is following other studies. 18,19 The presence of any chronic illness in the family was found to be significantly (p=0.003) associated with the presence of anxiety and it was in accordance with another study 20 . In the present study, ease to discuss problems with parents and perceiving unnecessary restrictions were both found to be significantly associated with anxiety (p<0.001) as well as depression (p=0.004), which was per the findings of another study.…”
Section: Discussionsupporting
confidence: 87%
“…6 The study conducted in Pokhara showed 21.7 % of adolescent psychosocial problems and likewise, the study conducted on central region of Nepal published in 2016 showed 17.03%. 17,20 Another study conducted in Dehradun, India showed a prevalence of 40.5% whereas a cross-sectional study in Muzaffarnagar, India, revealed that the overall prevalence of psychosocial problems among adolescent was found to be 41.43%. 21,22 There was no association found between age group, sex, ethnicity and educational status of participants with psychosocial problems.…”
Section: Discussionmentioning
confidence: 99%
“…This similar study showed that large proportion of the respondent 74.23% were using internet in mobile which is consistent with this study as majority 70.5% of the respondents were using mobile Phone and they are using it in the evening . 10 The respondents were using internet in mobile it may because of availability and affordability with the widespread adoption of home computers and smart phones and easy access to internet package of 3G/4G scheme on mobile phone. About 47.7% were male in this study which is consistent with the literature is the large susceptibility for males to be addicted to the Internet [11][12][13][14][15] whereas study conducted by Gupta et al contradicts the findings as female were more addicted to internet.…”
Section: Discussionmentioning
confidence: 99%